Beyond Rationality: A Systematic Literature Review of Overconfidence Bias in Investment Decision-Making from a Behavioral Finance Perspective - Ni Luh Reni Martini (PT. Global World Scientific, 2026)
The development of global financial markets, the digitalization of investment services, and the increasing participation of retail investors have changed the characteristics of investment decision-making. Under these conditions, investment decisions are no longer solely influenced by rational analysis as assumed in traditional financial theory, but are also influenced by various psychological biases, particularly overconfidence. This bias encourages investors to overestimate their abilities, knowledge, and predictive accuracy, potentially resulting in suboptimal investment decisions. This study aims to systematically synthesize the development of literature on the influence of overconfidence on investment decisions from a behavioral finance perspective, identify dominant research themes, evaluate the consistency of empirical findings, and uncover research gaps that still require development. The study used a Systematic Literature Review (SLR) approach with reference to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The literature selection process was carried out on articles published between 2015 and 2024 through the Scopus, ScienceDirect, SpringerLink, Taylor & Francis, and Google Scholar databases, resulting in ten articles that met all inclusion criteria for analysis. The synthesis results indicate that overconfidence is a significant determinant of investment decision-making. Five key themes were identified: the influence of overconfidence on investment activity intensity, increased risk appetite, the influence of demographic characteristics such as gender and generation, the role of investment digitalization in reinforcing behavioral biases, and the consistency of overconfidence across developing countries. In addition to strengthening the relevance of behavioral finance as an approach capable of explaining the limitations of investor rationality assumptions, this study also demonstrates that digital transformation has the potential to reinforce the illusion of knowledge and the illusion of control, thereby increasing investors' tendency to make more aggressive investment decisions. This study provides theoretical contributions by mapping the development of the literature on overconfidence and provides practical implications for investors, regulators, and digital investment platform developers in designing strategies to mitigate behavioral biases and strengthen financial literacy. Furthermore, this study identifies the need for longitudinal research and the development of models that integrate financial literacy, financial technology, artificial intelligence, and risk tolerance to broaden understanding of investment behavior in the era of digital transformation.